Stephen Spender, the 1930s, and Spanish Writing - Callahan, David (Miscelánea: A Journal of English and American Studies, 2005)
During the Spanish Civil War, the English literary world constructed important meanings about itself through its response to the conflict, a war in which the future of European Writing itself was being decided. One of the overlooked facets of this response involves the reading of and responding to Spanish writers on the part of the literary worlds for which the war was so significant. At the forefront of this encounter with Spanish writers in Britain was Stephen Spender, whose ensuing processing of what he found constitutes the most significant mediation of Spanish literature during the duration of the Civil War. This article examines Spender’s articulation of Spanish writing both in terms of the English literary world of the time and his own poetic development. Particular attention is paid to his response to and translations of Lorca. While Spender’s contacts, appreciation and translations of Spanish writers did not occasion noticeable alterations in his own work, but rather the solidifying of his beliefs about the nature of poetry and the role of the poet, the examination of this confluence of the poetry and politics of the 1930s reveals the stress points between a supposedly European politics of literary witness and the difficulties in absorbing literary traditions with which English writers were not familiar.